AIDS melodrama now: Queer tears in It's a Sin and Pose. (February 2023) - Duckels, Gabriel
This short article compares the British TV show It's a Sin and the American TV show Pose as landmark new examples of AIDS melodrama – a genre of tear-jerking, mass-market AIDS narrative which has renewed popularity due to contemporary investment in the queer histories of AIDS in the United Kingdom and the United States. While both shows deploy melodramatic aesthetics to stage the grief, virtue, and injustices endured by queer people living with HIV/AIDS in London and New York City prior to the arrival of antiretroviral medication, I argue that the squeezed budget and truncated format of It's a Sin – reduced from a longer series, to eight episodes, to five episodes – means that each episode builds towards the climax of the dead gay male body in anachronistic, contradictory ways. By contrast, I find that the lush excess of Pose transcends realism to dodge stereotypes of Black suffering and construct a queer history of AIDS in New York that is not reliant on the white gay male imaginary; a variation of what Saidiya Hartman calls critical fabulation. This short article thus aims to show that the cultural politics of melodrama remain central to the representation of AIDS history, and that AIDS melodrama can be a radical as well as reductive or ambivalent genre.